2018
DOI: 10.1016/j.celrep.2017.12.067
|View full text |Cite
|
Sign up to set email alerts
|

Peroxisome Proliferator Activated Receptor Gamma Controls Mature Brown Adipocyte Inducibility through Glycerol Kinase

Abstract: Peroxisome proliferator-activated receptors (PPARs) have been suggested as the master regulators of adipose tissue formation. However, their role in regulating brown fat functionality has not been resolved. To address this question, we generated mice with inducible brown fat-specific deletions of PPARα, β/δ, and γ, respectively. We found that both PPARα and β/δδ are dispensable for brown fat function. In contrast, we could show that ablation of PPARγ in vitro and in vivo led to a reduced thermogenic capacity a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
61
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 89 publications
(69 citation statements)
references
References 50 publications
7
61
0
1
Order By: Relevance
“…We exclusively investigated here the role of the mevalonate pathway in mature brown adipocytes and in the conversion of white into brown adipocytes, and we could show that statins reduce thermogenic function and PPARg levels, without affecting the number of differentiated cells. We have recently shown that PPARg is required to maintain the thermogenic capacity of mature brown adipocytes (Lasar et al, 2018); thus it is possible that statins inhibit BAT function through regulation of this factor.…”
Section: Discussionmentioning
confidence: 99%
“…We exclusively investigated here the role of the mevalonate pathway in mature brown adipocytes and in the conversion of white into brown adipocytes, and we could show that statins reduce thermogenic function and PPARg levels, without affecting the number of differentiated cells. We have recently shown that PPARg is required to maintain the thermogenic capacity of mature brown adipocytes (Lasar et al, 2018); thus it is possible that statins inhibit BAT function through regulation of this factor.…”
Section: Discussionmentioning
confidence: 99%
“…Brown adipose tissue (BAT)-specific GR-knockout mice (GR BATKO ) were generated by crossing Ucp1Cre ERT2 mice [36,37] with floxed GR mice. Knockout was induced in adult male animals by injection with 2 mg tamoxifen per day, for five consecutive days.…”
Section: Animalsmentioning
confidence: 99%
“…Another protein involved in transgenerational regulation is PPARγ, which is the master transcription factor for both white and brown adipogenesis and is involved in brown adipocyte development and thermogenic gene regulation [64,65]. Offspring with obese mothers have persistently lower PPARγ expression due to higher epigenetic repression, such as DNA hypermethylation and fewer active histone markers, at the Pparg promoter region [66].…”
Section: Dna Methylation In Intergenerational and Transgenerational Bmentioning
confidence: 99%